PENGARUH EKSTRAK AIR DAN ETANOL Alpinia spp. TERHADAP AKTIVITAS DAN KAPASITAS FAGOSITOSIS SEL MAKROFAG YANG DIINDUKSI BAKTERI STAPHYLOCOCCUS EPIDERMIDIS SECARA IN-VITRO - Wulansari, Dewi; Chairul, Praptiwidan (BERITA BIOLOGI, 2009)
Ellianol 70% and water exlracls of Alpinia spp. i.e. Alpinia zemmbei. A. kaisumadai. A. malaccensis and A. officinarum were examined for their impact in in-vitro phagocytosis activity and capacity of mouse (Mus musculus) peritoneum macrophage induced by Staphylococcus epidermidis.The extract concentrations used in this experiment were 0: O.I: 1.0: 10: 100: and 1000 µg/ml,Imboost (Echinacea pwpurea extract) 1000 µg/ml was used as positive control while distilled water as negative control.The assay results showed that all of the extracts were active to promote phagocytosis activity and capacity of macrophage cells.The phagocytosis acitivity and capacity were increased by increasing extract concentration, and ethanol extract showed better activity than water extract. Alpinia officinarum and A. kaisumadai extracts reveal better phagocytosis activity and capacity than others. Activity and capacity of phagocytosis of each concentration was significantly (P<0.05) different each other as well as with negative control. There is significant difference among each extracts and positive control at 1000 µg/ml